Reconstructing Innovation Diffusion in Public Health Sertvices: Evidence from Post-Treatment Care Policy in Bengkulu City - Novliza Eka Patrisia; Hardi Warsono; Kismartini Kismartini; Reni Shinta Dewi (Journal Public Policy, 2026)
This study aims to analyze the process of health service innovation diffusion in the Bengkulu City Government, analyze the supporting and inhibiting factors in the process of health service innovation diffusion in the Bengkulu City Government, recommend the right model for the process of health service innovation diffusion in Bengkulu City. This type of research is qualitative with a descriptive approach, involving informants from the community and 5 service officers. The data sources in this study consist of primary and secondary data, with data collection techniques through observation, in-depth interviews, and documentation carried out directly by the researcher. Data analysis techniques include data condensation, data presentation, and drawing conclusions. Data validity testing uses data triangulation techniques. This study proves that health service innovation diffusion is determined by the knowledge and persuasion stages, which directly improve decision-making certainty, implementation effectiveness, and accurate confirmation of expected health service outcomes. In addition, community acceptance and understanding of innovation are also important findings that must be encouraged through various outreach and mentoring activities in the field. As organic intellectuals, communities hold a strategic role not merely as recipients but as active triggers and initiators of innovation, underscoring the need for policies that systematically mobilize community capacity to drive sustainable health service innovation diffusion.